2017
DOI: 10.3847/1538-4357/aa653f
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Adenine on the Martian Surface in the Presence of Perchlorates and Ionizing Radiation: A Reflectron Time-of-flight Mass Spectrometric Study

Abstract: The aim of the present work is to unravel the radiolytic decomposition of adenine (C 5 H 5 N 5) under conditions relevant to the Martian surface. Being the fundamental building block of (deoxy)ribonucleic acids, the possibility of survival of this biomolecule on the Martian surface is of primary importance to the astrobiology community. Here, neat adenine and adenine-magnesium perchlorate mixtures were prepared and irradiated with energetic electrons that simulate the secondary electrons originating from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 96 publications
(152 reference statements)
1
11
0
1
Order By: Relevance
“…Finally, the model does not consider the effects of minerals common to the surface of Mars that are not present in our analog samples, most egregiously the presence of perchlorates in the martian regolith (Carrier and Kounaves, 2015). While we acknowledge the importance of perchlorate minerals, and the complexity of perchlorate mineral interactions with organic matter (Góbi et al, 2017;Fornaro et al, 2018), postulating how it may affect the kinetics of organic matter preservation in the studied environments is beyond the scope of this study.…”
Section: Implications Of Kinetic Modelingmentioning
confidence: 99%
“…Finally, the model does not consider the effects of minerals common to the surface of Mars that are not present in our analog samples, most egregiously the presence of perchlorates in the martian regolith (Carrier and Kounaves, 2015). While we acknowledge the importance of perchlorate minerals, and the complexity of perchlorate mineral interactions with organic matter (Góbi et al, 2017;Fornaro et al, 2018), postulating how it may affect the kinetics of organic matter preservation in the studied environments is beyond the scope of this study.…”
Section: Implications Of Kinetic Modelingmentioning
confidence: 99%
“…However, ionizing radiations can decompose perchlorate even at low temperatures, producing several lower oxidation state oxychlorine species, like chlorate (ClO 3 − ), hypochlorite (ClO − ), and chlorine dioxide (ClO 2 ), as well as molecular oxygen that remains trapped in the salt crystal [133], and atomic oxygen [134] or chlorite radicals (ClO 2 •) [135]. Such reactive species, in turn, may be responsible for the degradation of organic matter [133,136,137,138]. Interestingly, the SAM instrument indicated the presence of oxychlorine phases in Gale Crater, but the CheMin X-ray diffractometer was not able to detect them [139].…”
Section: Preservation Of Biosignaturesmentioning
confidence: 99%
“…This observation can be explained if the oxychlorine in Gale Crater is poorly crystalline, or its concentration is below the 1 wt% detection limit of CheMin , which means that the concentration of oxychlorine species may vary across the planet. Unfortunately, only a few studies have been reported in the literature about the effect of irradiation on the stability of organic molecules in the presence of perchlorates [136,137], while many studies have tried to reproduce the pyrolysis results of the Viking, Phoenix, and MSL missions (see Lasne et al [125], and references therein).…”
Section: Preservation Of Biosignaturesmentioning
confidence: 99%
“…The FTIR was operated in absorption-reflection-absorption mode at a reflection angle of 451 to the substrate normal in the mid-IR region from 5000 to 500 cm À1 with a resolution of 4 cm À1 at 2 minute intervals, which allowed collection of 30 spectra during the one hour of irradiation with 5 keV electrons. [91][92][93][94] Following the irradiation phase the ice was held isothermal at 5 K for one hour. Next, the substrate was heated to 300 K through a controlled ramp rate of 0.5 K min À1 (temperature programmed desorption; TPD).…”
Section: Methodsmentioning
confidence: 99%